Captains' response to a declining stock as anticipated in the surfclam (Spisula solidissima) fishery on the U.S. Mid-Atlantic coast by model evaluation. (December 2016) - Powell, Eric N.; Klinck, John M.; Hofmann, Eileen E.; Moreno, Paula; Kuykendall, Kelsey M.; Munroe, Daphne M.; Mann, Roger
Abstract: Mid-Atlantic Bight (MAB) warming accompanied by a decline in recruitment has slowly reduced surfclam abundance. Simulations examined fishery dynamics during an extended period of low recruitment followed by stock recovery after a high-recruitment event. The model assigned performance characteristics to each vessel and gave captains defined behavioral proclivities including a tendency to search, to communicate with other captains, to use survey data, and to integrate variable lengths of past-history performance in targeting fishing trips. During the simulated excursion in abundance, LPUE (landings per unit effort) declined as lower abundance required an extended time at sea to catch a full load. Captains expanded their geographic range of interest steaming farther from port in an effort to maintain their performance. Net revenue declined. Use of survey data significantly improved performance. About equal in positive effect was moderate searching. Other behaviors incurred penalties. Communication failed to improve performance because both poor and good information was transferred. Reliance on a long period of catch history failed to improve performance because information was out of date during a time of rapidly changing conditions. In these simulations, no captains' behaviors prevented a collapse in vessel economics at low abundance, but certain behaviors limited the degree and duration of economic dislocation. Highlights: Mid-Atlantic Bight warming accompanied by a decline in recruitment has slowly reduced surfclam abundance. A management strategy evaluation simulated fishery dynamics during a period of low recruitment followed by stock recovery. As abundance declined, LPUE declined, captains expanded their geographic range of interest, and net revenue declined. No captains' behaviors prevented a collapse in vessel economics at low abundance. Certain captains' behaviors limited the degree and duration of economic dislocation during abundance decline and recovery.